Identification And Binding Characterisation Of Peptide-Bearing Phages Towards Recombinant Protease (Ns6) Of Murine Norovirus - Soid, Nur Sakinah (2019)
Norovirus infections are considered the most common causes of epidemic and sporadic cases of acute gastroenteritis worldwide. To date, there are no licensed therapeutic intervention measures either in terms of vaccines or drugs available for these highly contagious human pathogen. Targeting non-structural viral protein such as protease is relevant due to their well conserved regions along with its critical functions in viral replication. In this study, the active site mutant version of MNV NS6 protease (C139A NS6) was cloned, overexpressed and purified before being used as target in biopanning/selection employing the Ph. D-7TM Phage Display Peptide Library kit (NEB) which was validated in streptavidin panning. After six rounds of biopanning, several peptide phages that are specific towards C139A NS6 were isolated and identified successfully. Upon identification of peptide phage, the peptide sequences were screened using online peptide databases and results indicated that all the sequences were unique and did not possess common motif with any published peptides to date. Three peptide phage clones with highest number of hits were tested for their binding specificity towards purified C139A NS6 using ELISA. It was observed that clones carrying peptide sequence QTEKNPL had the highest binding affinity towards C139A NS6 as compared to other clones and irrelevant phage control. Tertiary structure of C139A NS6 and binding interaction of the selected peptides (ADARYKS, QTEKNPL and NSKLVLG) with C139A NS6 receptor were predicted using I-TASSER and CABS-dock software, respectively.